URBAN DEVELOPMENT RANGES OF RURAL SETTLEMENTS OF THE STEPPE ZONE OF EUROPEAN RUSSIA - Vadim P. Petrishchev; Polina A. Kosykh (Юг России: экология, развитие, 2018)
Aim. The steppe zone is not only a unique natural and geographical formation, but also within the framework of European Russia a special region with specific socio-economic and demographic processes. In this article, we consider the issues of town-planning ranking of rural settlements on the basis of comparing the dynamics of their population as the most unique of all socio-economic indicators. Methods. To assess the dynamics of the population, we used the difference in population numbers over a five-year period from 2012 to 2016. When ranking settlements on the dynamics trend, 7 groups were identified, the results were mapped and analyzed. Results. Town-planning ranking has made it possible to identify the most depressive regions that gravitate toward the peripheral territories of the regions, join the borders of neighboring entities, and also form a "frontier" along the Russian-Kazakh border. The most promising areas are located in the south-west of the region under consideration (Krasnodar, Stavropol Krai, south of the Rostov region), where favorable economic and natural-climatic conditions are combined. In addition, promising rural settlements gravitate toward the administrative centers of the regions. Main conclusions. Based on the ranking we have identified trends in the decline of socio-economic indicators from west to east, the negative impact of the Russian-Kazakh border and the periphery of the territory, the growth of prospects towards the Black Sea coast, as well as "urbanization polarization", expressed in the compression of the regional urban space to urbanized centers.